2011
DOI: 10.1084/jem.20102149
|View full text |Cite
|
Sign up to set email alerts
|

Memory/effector (CD45RBlo) CD4 T cells are controlled directly by IL-10 and cause IL-22–dependent intestinal pathology

Abstract: Interleukin-10 acts directly on CD45RBlo but not CD45RBhi cells to control colitis upon transfer into Rag1-deficient recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 40 publications
6
174
2
1
Order By: Relevance
“…Thus, IL-22 has been reported to have protective effects against Citrobacter rodentiumeinduced inflammation, 36 in the spontaneous colitis arising in T-cell receptor-a À/À mice, 44 and in colitis induced by dextran sulphate sodium or by transfer to Rag À/À mice of CD45RB high CD4 þ T cells. 45 Conversely, IL-22 has been demonstrated to contribute to the colitic response in Rag À/À mice given Tregulatory celledepleted CD45RB low CD4 þ T cells, 46 in antieCD40-induced colitis, 47 and in the inflammatory response in the small intestine after Toxoplasma gondii infection. 48,49 Thus, IL-22 may have either beneficial or pathological roles in the intestine, depending on the nature of the immune insult.…”
Section: Th17 Cytokines In H Hepaticus Colitismentioning
confidence: 99%
“…Thus, IL-22 has been reported to have protective effects against Citrobacter rodentiumeinduced inflammation, 36 in the spontaneous colitis arising in T-cell receptor-a À/À mice, 44 and in colitis induced by dextran sulphate sodium or by transfer to Rag À/À mice of CD45RB high CD4 þ T cells. 45 Conversely, IL-22 has been demonstrated to contribute to the colitic response in Rag À/À mice given Tregulatory celledepleted CD45RB low CD4 þ T cells, 46 in antieCD40-induced colitis, 47 and in the inflammatory response in the small intestine after Toxoplasma gondii infection. 48,49 Thus, IL-22 may have either beneficial or pathological roles in the intestine, depending on the nature of the immune insult.…”
Section: Th17 Cytokines In H Hepaticus Colitismentioning
confidence: 99%
“…In chronic gastrointestinal infection or acute stimulation with chemical carcinogens, IL-17-producing IL-23R + ILC3s induce gut tumourigenesis through the IL-23/IL-17 signalling pathway, which promotes angiogenesis and tumour metastasis (54,55). Some experiments suggested that IL-22 producing ILC3s promote inflammation in active intestinal diseases (33,(56)(57)(58). IL-22 may promote pro-and anti-tumour mechanisms depending on the tissue microenvironment and tumour characteristics.…”
Section: The Role If Ilcs In Tumour Growth and Progressionmentioning
confidence: 99%
“…Another mouse model of colitis, which is induced by the transfer of naïve T cells into a lymphopenic host, is dominated by Th1 cells. This colitis model is characterized by IFN-dependent mucosal ulceration in the colon [136,137]. Th17 cell-dominated intestinal pathology is characterized by mucosal hyperplasia but not ulceration [76,136,138].…”
Section: Breakdown Of the Immune Homeostasis In The Intestinementioning
confidence: 99%
“…This colitis model is characterized by IFN-dependent mucosal ulceration in the colon [136,137]. Th17 cell-dominated intestinal pathology is characterized by mucosal hyperplasia but not ulceration [76,136,138]. IL-22, a signature cytokine of Th17 cells, can promote epithelial cell survival and proliferation.…”
Section: Breakdown Of the Immune Homeostasis In The Intestinementioning
confidence: 99%
See 1 more Smart Citation